Perception of teamwork and social skills in university students - Sánchez-Paredes, Rubén Guillermo (2022)
The ability to work in a team and other social skills are required in professionals and for this reason universities promote their development through comprehensive training. The objective of the study was to establish the relationship between teamwork and social skills in university students. A quantitative, descriptive, correlational, non-experimental and cross-sectional study was carried out with a non-probabilistic and intentional sample of 73 males and 83 females. Two scales were developed and validated by expert judges with Cronbach's alpha reliability of .967 and .977, respectively. A moderate positive correlation was found between Teamwork and social skills (rs = 0.678) as well as with its dimensions Leadership, Communication, Decision-making and Problem-solving. The perception of teamwork as a teaching-learning strategy has been related to the development and practice of social skills.